Members and Nonmembers: Determinants of Dues-Paying Membership in a Bargaining Unit - McClendon, John (Relations industrielles / Industrial Relations, 2000)
This study builds on the union organizing and free-rider literature by examining determinants of dues-paying membership in the Temple Association of University Professionals (TAUP). The TAUP, an American Federation of Teachers affiliate, is the collective bargaining representative for 992 members of the Temple University faculty, 52 percent of whom are dues-paying members. Results indicate that attitudes about unions in general, the costs of union dues, the perception of alternative faculty governance effectiveness, and beliefs about the appropriateness of unionization for professional employees were related to joining behaviour. In contrast, job attitudes, attitudes about the employer, perceived bargaining unit effectiveness, and political ideology were not significant predictors of membership status.